Making "making money": A discussion with Ole Bjerg - Ole Bjerg; Stephen Dunne (Finance and Society, 2015)
Stephen Dunne recently sat down with Ole Bjerg to chair a discussion about his new book Making Money: The Philosophy of Crisis Capitalism (Verso, 2014). We publish an elaborated version of the book's concluding chapter - 'Life after Debt' - within this special issue. This interview and question and answer session puts Ole's argument there, as well as the arguments of his book more generally, into a broader context.
Keywords: 300; Money; debt; philosophy; crisis; capitalism; revolution